PHOTOCATALYTIC DEGRADATION OF REACTIVE RED DYE AND OPTIMIZATION OF THEIR EXPERIMENTAL FACTORS - Olabode Victor O.; Alogala J.A.; Okon U.E.; Jinaidu Haruna M.; Gamde; G.G.; Jahkeng Williams E (Journal CleanWAS)
Box-Behnken design of experiment for the optimization of the experimental parameters of the photocatalytic degradation of reactive red dye using dye concentration (mg/L), catalyst dosage (mg/L), pH and time of exposure as experimental factors was studied and reported. Stock solution of reactive red dye was prepared (0.00001M) and serial dilution was used to prepare twenty-seven (27) different concentration of the dye solution which were subjected to photocatalytic degradation in a photo reactor using a ultraviolent light source under ambient environmental condition. The absorbances of these solutions before and after photo degradation was taken to obtain different percentage degradation for each experimental run. Analysis of these results was carried out using minitab 17 computer software. The result reveals the optimized conditions for the photodegredationas 10mg/L (dye concentration), 1mg/l (catalyst dosage), 5.85 pH and 90 minutes (time of exposure). This was confirmed experimentally after the optimization to prove that minitab17 software is highly effective for the optimization.